Penanaman nilai edupreneurship dalam pembelajaran projek penguatan profil pelajar pancasila (P5) di sekolah dasar - Lutvita, Nadea Rosi; Karsono, Karsono (Didaktika Dwija Indria, 2026)
This research aims to describe and explain the implementation of edupreneurship values in the Pancasila Student Profile Strengthening Project (P5) at SD Negeri Kemasan I Surakarta. The qualitative approach used is descriptive qualitative. This study employs purposive sampling techniques. Data collection was conducted using observation, interviews, and documentation of P5 learning activities at SD Negeri Kemasan 1 Surakarta, Grade 5, which represent edupreneurship values including independence, creativity, collaboration, willingness to take risks, self-confidence, and leadership qualities. Additionally, data from the school profile of SD Negeri Kemasan I Surakarta and school reports related to the implementation process of P5 learning were utilized. Data analysis in this study used the Interactive Analysis technique by Miles & Huberman. Validity testing was conducted using content and language validity through expert judgment. The research results indicate that the P5 Learning Program at SD Negeri Kemasan 1 Surakarta successfully fosters the six core values of edupreneurship: independence, creativity, collaboration, risk-taking, self-confidence, and leadership. These values form an important foundation for students in facing future challenges.